Relocation of Rempang residents due to state-owned land - Firdaus, Faris Ahlul; Antikowati, Antikowati; Fadhilah, Nurul Laili (University of Merdeka Malang, 2024)
The government's obligation is to manage land for public and private purposes in accordance with the mandate of Article 33 Paragraph (3) of the 1945 Constitution which states that land, air and natural resources are controlled by the state for the greatest prosperity of the people. The relocation of Rempang residents became news that was conveyed because it received resistance from local residents and was a resonant action as a result of Presidential Decree Number 41 of 1973 which stated that the management rights of Batam Island were handed over to the Batam Authority, which means that the entire island area located on Batam Island was handed over with rights status management to Batam authorities. The legal issues raised by the author are first, how is the relocation of Rempang residents over control of state-owned land and second, what are the legal consequences of the relocation of Rempang residents over control of state-owned land. The aim to be achieved by this author is to analyze the implementation of the relocation of Rempang residents over control of stateowned land and to analyze the legal results of the relocation of Rempang residents over control of state-owned land.